Dexmedetomidine for delirium prevention after cardiac surgery: An updated systematic review and meta-analysis with trial sequential analysis - Caetano da Silva, Lucas; Tapioca, Vanessa; Viana, Patricia; Pereira, Eduardo Maia; Gibicoski, Tathiane; Amaral, Sara (Anaesthesia critical care & pain medicine, 2025)
[Display omitted] •Postoperative delirium remains a significant issue following cardiac surgery, impacting patient outcomes and healthcare costs.•Conflicting evidence in recent studies prompted an updated review to evaluate the effectiveness of dexmedetomidine in preventing delirium.•This meta-analysis of 31 studies suggests that dexmedetomidine significantly reduces the incidence of delirium, supported by robust methods like TSA.•While dexmedetomidine shows benefits, careful monitoring of side effects is crucial in high-risk patients. Postoperative delirium remains a common complication after cardiac surgery. The impact of dexmedetomidine (DEX) on preventing postoperative delirium is still controversial as recent randomized controlled trials (RCTs) have presented conflicting results. We conducted an updated systematic review and meta-analysis of RCTs evaluating DEX efficacy in preventing delirium after cardiac surgery. A systematic search of MEDLINE, Embase, and Cochrane databases identified RCTs comparing DEX with placebo or other treatments in patients aged ≥18 years. Sensitivity, subgroup analyses, and trial sequential analysis (TSA) assessed the robustness of the findings. A total of 31 RCTs including 5628 patients were analyzed, 50.1% of them receiving DEX. Delirium incidence was significantly lower in the DEX group (RR 0.61; 95% CI, 0.49–0.75; P < 0.001). This protective effect remained across subgroup analyses based on age, control type, delirium assessment method, and after excluding trials at high risk of bias. DEX use was associated with a shorter intensive care unit length of stay (MD −0.14 days; 95% CI, −1.28 to −0.04; P < 0.01). TSA confirmed the result’s robustness. However, DEX increased bradycardia risk (RR 1.53; 95% CI, 1.05–2.21; P = 0.02). No significant differences were found in mortality, intubation duration, hospital length of stay, atrial fibrillation, or hypotension. Dexmedetomidine significantly reduces postoperative delirium following cardiac surgery, with moderate evidence confirmed by TSA. While it demonstrates clinical benefits, careful bradycardia monitoring is warranted. PROSPERO (CRD42024593472).